Pattern Recognition and Machine Intelligence 10th International Conference, PReMI 2023, Kolkata, India, December 12-15, 2023, Proceedings - Maji, Pradipta; Huang, Tingwen; Pal, Nikhil R.; Chaudhury, Santanu; De, Rajat K. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
The LNCS volume constitutes the refereed proceedings of 10th International Conference, PReMI 2023, in Kolkata, India, in December 2023. The 91 full papers, presented together with abstracts of 6 keynote and invited talks, were carefully reviewed and selected from more than 300 submissions. The conference presents topics covering different aspects of pattern recognition and machine intelligence with real life state-of-the-art applications.
Pattern Recognition -- Machine Learning -- Deep Learning -- Statistical Learning -- Cognitive Computing -- Computational Intelligence -- Medical Imaging -- Image and Video Processing -- Computer Vision -- Soft Computing -- Information Security -- Signal Processing -- Computational Neurology -- Biometrics -- Bioinformatics.
Keywords: Pattern recognition systems; Computer vision; Automated Pattern Recognition; Computer Vision